2021
DOI: 10.32890/gbmr2021.13.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Corporate Environmental Accounting Disclosure of Oil and Gas Firms in Nigeria

Abstract: This study examines the cognitive factors that determine corporate environmental accounting disclosures (CEAD). The population consists of all the fourteen (14) listed oil and gas firms in Nigeria. Panel data were obtained from the annual reports and accounts of the firms for the period of 2010 to 2019. A correlational research design was used and the data were analyzed using the Generalized Least Square regression (random model). The study found that firm size; leverage and multi-national companies have posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Another recent study related to Nigerian oil and gas companies by Bala and Lawal (2021) highlighted that ROA has a positive but insignificant impact on CEAD, firm size has a positive and significant effect on CEAD, and leverage was statistically found to have a positive and significant influence on CEAD, they concluded that any increase or decrease in the proportion of leverage will have an increasing or decreasing effect on CEAD. In the case of China, companies' environmental sensitivity and size are apparently the major components that are affecting their environmental disclosure practices, and the study proposed that financial performance is not significantly related to environmental disclosure practices (Liu and Anbumozhi, 2009).…”
Section: Environmental Accounting Disclosure Practices Depend Upon Fi...mentioning
confidence: 99%
“…Another recent study related to Nigerian oil and gas companies by Bala and Lawal (2021) highlighted that ROA has a positive but insignificant impact on CEAD, firm size has a positive and significant effect on CEAD, and leverage was statistically found to have a positive and significant influence on CEAD, they concluded that any increase or decrease in the proportion of leverage will have an increasing or decreasing effect on CEAD. In the case of China, companies' environmental sensitivity and size are apparently the major components that are affecting their environmental disclosure practices, and the study proposed that financial performance is not significantly related to environmental disclosure practices (Liu and Anbumozhi, 2009).…”
Section: Environmental Accounting Disclosure Practices Depend Upon Fi...mentioning
confidence: 99%
“…Oil and gas firms in Nigeria are becoming increasingly concerned about EAD (Ja'afar et al, 2021). Although the oil sector is important to Nigeria's economy, it also has a great impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Said R also believed that accounting information disclosure would directly affect a company's strategic management [7]. Bala H proposed that large companies in Nigeria need to expand the scale of accounting information disclosure [8]. Gomes P believed that accounting information disclosure is an important link in the reform of international public sector accounting standards [9].…”
Section: Introductionmentioning
confidence: 99%